Analysis of Factors Influencing Female Labor Force Absorption in Java During the 2014-2023 Period - Norasida, Azira; Syafitri, Wildan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Female labor plays an important role in achieving sustainable and inclusive economic welfare in a country. Labor absorption is a factor that can help in looking at the role of the female workforce. Until now, there is still an imbalance in the absorption of female labor in Java Island, which is the island with the highest economic growth in Indonesia. The occurrence of this imbalance can be influenced by several factors. This study aims to determine the effect of population, economic growth, education, digitalization, and wages on female employment. The sample of this research is 6 provinces in Java during 2014-2023. This research uses an associative quantitative approach with secondary data sourced from BPS. The method used is panel data regression and processed with e-views. The results showed that population and education had a significant positive effect, wages had a significant negative effect, economic growth had an insignificant negative effect, and digitalization had an insignificant positive effect.